ANALYSIS OF FACTORS AFFECTING UNEMPLOYMENT RATE IN NORTH SUMATRA PROVINCE - Stellamaris Metekohy; Silvia Ekasari; Anton Yuliansyah; Aminah Lubis; Nur Jannah Nasution (Bajang Institute, 2023)
This study aims to determine and analyze factors affecting unemployment rate in North Sumatra Province. This type of research uses quantitative research. Secondary data is sourced from the official publication of the Central Bureau of Statistics for North Sumatra Province. The observation period of this study is from 2000 to 2022. Hypothesis testing using partial test. The results show that investment has a positive and significant effect on unemployment rate in North Sumatra Province. Inflation has a positive and significant effect on unemployment rate in North Sumatra Province.